Analysis of Village Financial Management - Putri, Milania Hasya; Umar, Ahmad Riyadh (Indonesian Journal of Public Policy Review, 2023)
This study examines the financial management of Wedi Village in Gedangan District, Sidoarjo Regency, focusing on the alignment between the Annual Village Budget (APBDes) and the Village Medium-Term Development Plan (RPJMDes), the capacity of village officials in report preparation and financial accounting, and the proficiency of SISKEUDES application operators. Applying a qualitative approach, the research employs observations, interviews, and documentation for data collection. While the village demonstrates adherence to regulatory guidelines, hindrances include incomplete accommodation of community aspirations in the APBDes, conflicting central government regulations, and diminished village autonomy in financial management. The study highlights the need for streamlined regulations to enhance village financial autonomy and recommends targeted training programs for officials to address operational challenges in financial management. Highlight : Comprehensive Analysis: This study provides a thorough examination of the financial management practices in Wedi Village, shedding light on the compatibility issues between the APBDes and RPJMDes, as well as challenges in utilizing the SISKEUDES application. Capacity Building: The research underscores the crucial need for targeted training programs for village officials, emphasizing the lack of skills in preparing accountability reports and financial accounting, thereby addressing a key obstacle in effective financial management. Autonomy Challenges: The study highlights the impact of overlapping central government regulations, reduced village autonomy, and the inability to accommodate all community aspirations in the APBDes, advocating for regulatory reforms to empower villages in managing their finances. Keywords: Village Financial Management, APBDes, RPJMDes, SISKEUDES Application, Regulatory Compliance